Critical Success Factor of Online Learning of Private University in the era of COVID-19 - Chaikalaya, Rattana (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: In 2019, China found a Virus. It was later named “COVID-19”, short for “Coronavirus Disease Starting in 2019”. The purposes of this research were: 1) to study the characteristics of private university students who succeeded in online learning in the era of COVID-19; 2) To study the level of critical success factors for online learning at private universities in the era of COVID-19. 3) To find out the success factors of online learning during the COVID-19 outbreak. Methodology: This study was quantitative in nature. The purposive sampling method was used to select 225 university students who were recruited via the Internet. Questionnaires were used to collect data. The data received were calculated and analyzed using descriptive statistics and confirmatory factor analysis (CFA). Results: The findings revealed that almost all of the characteristics of private university students who successfully studied online during the COVID-19 pandemic were female. With a GPA greater than 2.75, she prefers to use the Zoom application while studying at the Faculty of Business Administration. on time 4 pm - 8 pm. and level of opinion were teacher factors with a chi-square of 2/df = 1.21, P = 0.815, GFI = 0.989, AGFI = 0.966, NFI = 0.978, IFI = 0.988, CFI = 0.984, RMR = 0.003, RMSEA = 0.012, and each of these variables were consistent with the empirical data. Conclusion: In summary, the research underscores that successful online learning among private university students during the COVID-19 pandemic is associated with specific demographic and academic characteristics, a preference for certain study habits, and a pronounced emphasis on positive perceptions of instructor-related factors.